2017
DOI: 10.1038/s41598-017-06045-x
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of retinal morphological and functional decay in a light-inducible, rhodopsin mutant mouse

Abstract: Hallmarks of Retinitis Pigmentosa (RP), a family of genetic diseases, are a typical rod-cone-degeneration with initial night blindness and loss of peripheral vision, followed by decreased daylight sight and progressive visual acuity loss up to legal blindness. Great heterogeneity in nature and function of mutated genes, variety of mutations for each of them, variability in phenotypic appearance and transmission modality contribute to make RP a still incurable disease. Translational research relies on appropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(49 citation statements)
references
References 44 publications
4
45
0
Order By: Relevance
“…Iba1 is a calcium‐binding protein with a molecular weight of 17 kDa specifically expressed in macrophage/microglia (manufacturer's data sheet). A widely used microglial marker in mouse retina (Gargini et al, ; Guadagni et al, ) produces a staining pattern similar to what observed in our results.…”
Section: Methodssupporting
confidence: 90%
See 3 more Smart Citations
“…Iba1 is a calcium‐binding protein with a molecular weight of 17 kDa specifically expressed in macrophage/microglia (manufacturer's data sheet). A widely used microglial marker in mouse retina (Gargini et al, ; Guadagni et al, ) produces a staining pattern similar to what observed in our results.…”
Section: Methodssupporting
confidence: 90%
“…Photoinduction duration was controlled by a digital clock; during the procedure animals were fully awake and freely moving. Temperature did not change significantly during light exposure (Gargini et al, ). Animals were exposed to 12.000 lx light for 2 min, after which the animals were kept in the chamber in the dark for one additional minute (“cooldown” time) postinduction (PI), then returned to the local animal facility where they were kept in ambient light conditions (below 60 lx) on a 12/12‐hr light/dark cycle, with water and food ad libitum until the time of retinal examination.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subretinal autofluorescent spots observed in vivo by fundus examination in patients and in animal models are considered diagnostic markers for inflammatory responses in retinal damage and disease. 5660 To test whether NR treatment alters inflammatory responses of the LIRD mice, in vivo fundus examination at the level of the subretinal space was conducted one week following induction of retinal degeneration. Uninduced eyes showed few blue autofluorescent spots at the level of the subretinal space in vivo (Fig.…”
Section: Resultsmentioning
confidence: 99%